The Physics of Structural Phase Transitions - Fujimoto, Minoru; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2005)
Phase transitions in which crystalline solids undergo structural changes present an interesting problem in the interplay between the crystal structure and the ordering process that is typically nonlinear. Intended for readers with prior knowledge of basic condensed-matter physics, this book emphasizes the physics behind spontaneous structural changes in crystals. Starting with the relevant thermodynamic principles, the text discusses the nature of order variables in collective motion in structural phase transitions, where a singularity in such a collective mode is responsible for lattice instability as revealed by soft phonons. In this book, critical anomalies at second-order structural transitions are first analyzed with the condensate model. Discussions on the nonlinear ordering mechanism are followed with the soliton theory, thereby interpreting the role of long-range order. Relevant details for nonlinear mathematics are therefore given for minimum necessity. The text also discusses experimental methods for modulated crystal structures, giving examples of structural changes in representative systems. This book is divided into two parts. The first part includes such topics as the Landau theory of phase transitions, statistics, correlations, and the mean-field approximation, pseudospins and their collective motion, soft lattice modes, condensates and their nonlinear growth, and lattice imperfections and their role in phase transitions of real crystals. The second part discusses experimental studies of modulated crystals using X-ray diffraction, neutron inelastic scattering, light scattering, dielectric measurements, and magnetic resonance spectroscopy. While the presence of modulated structures in the critical region is not particularly suggested in the published results of these studies, it is notable that most observed anomalies indicate evidence for pinned pseudospin condensates.
Basic Concepts -- Thermodynamical Principles and the Landau Theory -- Order Variables, Their Correlations and Statistics: the Mean-Field Theory -- Collective Modes of Pseudospins in Displacive Crystals and the Born-Huang Theory -- Soft Modes, Lattice Anharmonicity and Pseudospin Condensates in the Critical Region -- Dynamics of Pseudospins Condensates and the Long-Range Order -- Experimental Studies -- Diffuse X-ray Diffraction and Neutron Inelastic Scattering from Modulated Crystals -- Light Scattering and Dielectric Studies on Structural Phase Transitions -- The Spin-Hamiltonian and Magnetic Resonance Spectroscopy -- Magnetic Resonance Sampling and Nuclear Spin Relaxation Studies on Modulated Crystals -- Structural Phase Transitions in Miscellaneous Systems.
Keywords: Condensed matter; Condensed Matter Physics